2020
DOI: 10.21608/adjg.2020.14217.1186
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Anticollagenolytic Agents on Dentin Erosion before and After Casein Phospho Peptides-Amorphous Calcium Fluoride Phosphate Application

Abstract: Purpose: This study aimed to compare the effect of two anticollagenolytic agents, chlorohexidine and Aloe vera on dentin microhardness and their effect as pretreatments on the remineralization potential of CPP-ACFP. Materials and Methods: For this study, 40 extracted sound human premolars were subjected to artificial erosion and randomly divided to two equal groups (20 premolars each) according to immersion in the tested anticollagenolytic agents (A); group (A 1) Aloe vera and group (A 2) Chlorhexidine. Each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This assessment method provides a simple, rapid, and non-destructive test. In addition, it is considered by many researches (21) . Percentage of change of dentin microhardness was used to assess recovery conducted for each sample through its life track before assessment, after demineralization, after treatment and then after different storage intervals.…”
Section: Discussionmentioning
confidence: 99%
“…This assessment method provides a simple, rapid, and non-destructive test. In addition, it is considered by many researches (21) . Percentage of change of dentin microhardness was used to assess recovery conducted for each sample through its life track before assessment, after demineralization, after treatment and then after different storage intervals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is considered by many researches. (11) Results of the microhardness mean values demonstrated that, there was statistically significant increase in microhardness after treatment in white tea and green tea groups.…”
Section: Comparison Between Different Intervals Was Performed Usingmentioning
confidence: 92%